Pengaruh Struktur Modal Dan Kinerja Keuangan Terhadap Nilai Perusahaan: Studi Empiris Pada Perusahaan Manufaktur Sektor Industri Dasar Dan Kimia Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2019 - Muhammad Saddam; Sarwani Sarwani (Jurnal Neraca Peradaban, 2021)
This study aims to determine the effect of capital structure and financial performance on firm value in the Basic Industry and Chemical Sector Manufacturing Companies listed on the Indonesia Stock Exchange. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study that capital structure has a significant effect on firm value by 37.0%. Hypothesis testing is obtained t count> t table or (7.661> 1.984). Financial performance has a significant effect on firm value by 22.1%, hypothesis testing is obtained t count> t table or (5.327> 1.984). Capital structure and financial performance simultaneously have a significant effect on firm value with the regression equation Y = 0.450 + 0.245X1 + 0.068X2 and the contribution of the effect is 47.5%, the hypothesis test obtained F count> F table or (44.827> 2,700).